2008
DOI: 10.1080/09540120701449112
|View full text |Cite
|
Sign up to set email alerts
|

HIV and family planning service integration and voluntary HIV counselling and testing client composition in Ethiopia

Abstract: Integrating voluntary HIV counselling and testing (VCT) with family planning and other reproductive health services may be one effective strategy for expanding VCT service delivery in resource poor settings. Using 30,257 VCT client records with linked facility characteristics from Ethiopian non-governmental, non-profit, reproductive health clinics, we constructed multi-level logistic regression models to examine associations between HIV and family planning service integration modality and three outcomes: VCT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Thus, it is positive that our study found that higher proportions of rural men in this age group had been tested. The higher test proportion found among younger than older rural men was in line with findings from other studies in SSA [11,13,16,48]. The association with younger age that remained after adjustment for education, marital status, knowledge, and sexual behaviour probably reflects the fact that older rural men have a lower self-perceived risk of HIV, but we had not information about this predictor [11].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, it is positive that our study found that higher proportions of rural men in this age group had been tested. The higher test proportion found among younger than older rural men was in line with findings from other studies in SSA [11,13,16,48]. The association with younger age that remained after adjustment for education, marital status, knowledge, and sexual behaviour probably reflects the fact that older rural men have a lower self-perceived risk of HIV, but we had not information about this predictor [11].…”
Section: Discussionsupporting
confidence: 88%
“…Interventions to increase HIV testing include task-shifting (testing through lay healthcare workers) [7779] and provider-initiated testing [8991] as well as mobile, community, home-based and workplace services 8387,92] which bring the service nearer to the patient and thus increase accessibility, which might in turn increase acceptability. Other interventions aimed to increase acceptability of testing are self-testing [80] and incentivized testing [93,94].…”
Section: Resultsmentioning
confidence: 99%
“…Integrating syphilis screening with family planning services, such as intrauterine device insertions, also represents another way of reaching older women. HIV testing has been successfully integrated with post-abortion and other family planning services in settings in Kenya [41], Ethiopia [42], Tanzania [43], and the U.S. [44] …”
Section: Discussionmentioning
confidence: 99%